Post-PhD Researchers' Trajectories and Networking: The Mediating Role of Writing Conceptions. (October 2021) - Castelló, Montserrat; Sala-Bubaré, Anna; Pardo, Marta
The present study used a longitudinal mixed-method design to investigate the relationship between post-PhD researchers' writing conceptions and their experiences, scholarly trajectory, and networking capabilities. A total of 134 Spanish post-PhD researchers answered the Post-PhD Experience— Survey scales on Academic Writing and Social Support . One year later, a subsample of 21 participated in retrospective multimodal interviews, in which visual methods (Journey and Network Plots) were applied to analyse their writing trajectories during this period of time. The person-centred analysis revealed three post-PhD profiles regarding writing conceptions and evidenced differences among them in the way they participate in the research community and interact with other researchers. Qualitative results suggest the post-PhD researchers in each profile position themselves in the community differently and subsequently engage in distinctive writing experiences. The study provides evidence of how writer profiles appear to mediate trajectories and networking, something not evident when using only sectional designs. Relational agency is revealed to be an important aspect of productive writers. Pedagogical implications are discussed, particularly the need to promote writers' awareness on how their writing conceptions intertwine with their strategic management of research writing practices in different contexts.